Approach to the Profile of Teaching Degree in Information and Documentation from the Complutense University of Madrid - Tejada Artigas, Carlos Miguel (2018)
There are studied the characteristics of the professorship of the grade in Information and documentation of the Complutense University of Madrid, such as: his number, his evolution, his distribution for categories, his use of the information technologies, his ownership to groups of research and his publications.